Influência da manipulação de fatores extrínsecos no controle da postura sentada em crianças com paralisia cerebral - Costa, Carolina Souza Neves da (2015)
The general objective is to investigate the manipulation of extrinsic factors on sitting postural control in children with Cerebral Palsy (CP). For better understanding we divided this thesis in 4 studies. Study 1 aims to systematically review studies evaluating sitting postural control in children with CP. We intend to describe the characteristics of sitting postural control, the methodological procedures used for analysis, and factors that influence it, and the main results of intervention protocols for sitting postural control in children with CP. In context of extrinsic factors studied, little is known about how children with CP use and integrate sensory information into motor activity in order to maintain postural orientation and stability. This gap in the literature guides the study 2. For that, in the Study 2, we investigate and compare sitting postural control under challenging visual and somatosensory inputs between typical children and children with CP with a Gross Motor Functional Classification System (GMFCS) levels I-IV. For that, 35 typical children and 36 children with spastic CP with GMFCS levels I (10), II (8), III (10) e IV (8) were recruited. Eletrocmyoghapy electrodes were placed billaterally properly on thoracal extensors, lumbar extensors and rectus abdominais. The children were asked to sit without back and foot support on a force plate (100Hz) placed on a bench. Participants’ hands are on their laps, and they fixated on a target located 1-m in front of them at eye level. To challenge somatosensory inputs, children sat on 30Kg/m3 (50x50cm) foam that was placed atop the force plate. Four randomized quiet sitting conditions namely eyes opened (EA), eyes closed (EF), foam surface and eyes opened (IA) and foam surface and eyes closed (IF). Each condition was maintained for 20 seconds for three times. There was a rest period of 30-50 seconds between each trial. The measures from force plate chosen were range displacement or amplitude for anterior-posterior (AP) and medial-lateral (ML) directions, AP and ML velocity and area of Center of Pressure (CoP). EMG variables were muscles activitiy (root-mean square - RMS) and muscle symmetry. When exposed to changes on somatosensory information added to eyes closed, children with CP GMFCS level III and IV present increased extensor muscles activity and musces asymmetry, reflecting their inability to reweight sensory information and increased dependence on somatosensory information for maintaining sitting balance when compared to typical children. In the Study 3, we investigate the immediate effects of wearing the suit on sitting posture in different sensory conditions in children with CP, comparing to typical children. For that, we used the same experimental protocol from study 2 and each condition was done with and without wearing an orthotic suit Pediasuit with bungee set up, individualized for each child. Nonlinear measures of CoP variability were added and analyzed by AP and ML approximate entropy (ApEn) and AP and ML Correlation Dimensional (CoD). Suit affects the control of sitting posture in children with CP with different GMFCS levels, decreasing amount of variability, but improves complexity and dimensionaty of degrees-of-freedom, especially in conditions demanding sensory adaptability. The objective of Study 4 was to compare the effect of biomechanical constraints (trunk support) on neural control of head stability during development of trunk control. We used an adjustable external support to isolate and differentiate the effects of biomechanical constraint on specific regions of the trunk. The posterior support was raised or lowered to allow evaluation of four different trunk segments: axillae support, mid-thoracic, waist support and hip support. Data from a previous cross-sectional study and longitudinal study of Saavedra et al. (2015) were used. However, we apply nonlinear measures (complexity –ApEN; dimesionality or CoD; predictability –LyE) specifically to head stability. The effect of external support varies depending on the child’s level of control and diagnostic status. Children with GMFCS V and young TD infants had better outcomes with external support, but external support was not enough to completely correct for influence of CP. Surprisingly, GMFCS IV responded with better outcomes below the level where trunk control was lost, suggesting that they used different compensatory strategies.